Colistin for the treatment of urinary tract infections caused by extremely drug-resistant Pseudomonas aeruginosa: a call for a dose update - Sorlí, Luisa (J Infect, 2019)
OBJECTIVES: Optimal dosage regimens of colistin for the treatment of urinary tract infections (UTI) are unknown. Colistimethate sodium (CMS), the inactive prodrug of colistin, is mainly excreted in urine and converts to colistin after filtration by glomeruli, suggesting that concentrations of colistin in urine could be much higher than in plasma. Therefore, there is a need to optimize dosage regimens of intravenous CMS for UTI. The aim of this study was to examine the relationship between AUC/MIC of formed colistin and clinical outcomes in patients with UTI caused by extremely drug resistant (XDR) Pseudomonas aeruginosa. METHODS: This prospective, observational cohort study involved patients with UTI caused by XDR P. aeruginosa. Clinical cure, bacteriological clearance and acute kidney injury (AKI) were analyzed. Steady-state colistin plasma concentrations (C(ss)) were measured using HPLC. Based on the PK/PD of colistin in neutropenic mouse thigh infection model with P. aeruginosa, the optimal AUC/MIC should be ≥60 mg·h/L. According to the pharmacokinetics (PK) in critically-ill patients, the C(ss) target of formed colistin in plasma was 2.5 mg/L. RESULTS: Thirty-three patients were included (24 lower UTI and 9 pyelonephritis). The MIC(50) and MIC(90) values for colistin were 0.5 and 2 mg/L respectively. Nineteen patients (57.6%) received colistin monotherapy (84.2% UTI and 15.8% pyelonephritis). Of these, clinical cure was achieved in 89.5% of cases. Among patients with clinical cure, only 5 (29.4%) attained an optimal plasma AUC/MIC and only 1 (5.9%) the therapeutic level of formed colistin (2.5 mg/L). However, 10 (58.8%) patients showed colistin plasma concentrations above the MIC of the isolated P. aeruginosa. Microbiological eradication was achieved in 76.9% of patients. AKI at the end of treatment was present in 29.4% of patients. CONCLUSIONS: The currently recommended dosage regimens of CMS showed high efficacy for the treatment of lower complicated UTI caused by XDR P. aeruginosa in non-critically ill patients and in the case of low MIC values, but also a considerable nephrotoxicity rate. Our data suggest that the use of lower CMS doses for lower UTI should be investigated in future studies to minimize the unnecessary nephrotoxicity.